2007
DOI: 10.1007/s10886-006-9235-4
|View full text |Cite
|
Sign up to set email alerts
|

Do Elevated Temperature and CO2 Generally Have Counteracting Effects on Phenolic Phytochemistry of Boreal Trees?

Abstract: Global climate change includes concomitant changes in many components of the abiotic flux necessary for plant life. In this paper, we investigate the combined effects of elevated CO 2 (720 ppm) and temperature (+2 K) on the phytochemistry of three deciduous tree species. The analysis revealed that elevated CO 2 generally stimulated increased carbon partitioning to various classes of phenolic compounds, whereas an increase in temperature had the opposite effect. The combined effects of both elevated CO 2 and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 32 publications
(49 reference statements)
2
35
1
Order By: Relevance
“…We use graphical vector analysis (GVA) to evaluate the relationship between foliar phytochemical synthesis, foliar phytochemical concentration and foliar biomass (Timmer & Stone ; Haase & Rose ; Gebauer, Strain & Reynolds ; Koricheva ; Veteli et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…We use graphical vector analysis (GVA) to evaluate the relationship between foliar phytochemical synthesis, foliar phytochemical concentration and foliar biomass (Timmer & Stone ; Haase & Rose ; Gebauer, Strain & Reynolds ; Koricheva ; Veteli et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…Thus, responses to enriched CO 2 may be: 1) independent of temperature (e.g., foliar nitrogen and phenolics in Angiosperms); 2) offset by elevated temperature (e.g., carbohydrates; foliar terpenes in gymnosperms); or 3) apparent only with elevated temperature (e.g., foliar nitrogen in gymnosperms, phenolics, and terpenoids in woody tissues). More recently, Veteli et al (2007) reported for three tree species (Betula and Salix) that carbon allocation to phenolics was increased under elevated CO 2 , decreased under elevated temperature, and unchanged under a combination of elevated CO 2 and temperature.…”
Section: Carbon Dioxidementioning
confidence: 99%
“…Meta-analysis is a tool that has been increasingly used to uncover general trends behind conflicting results from empirical studies (Leimu and Koricheva 2004). For instance, Stiling and Cornelissen (2007) and Veteli et al (2007) used meta-analysis to study CO 2 -mediated changes on phenolics in plants. Their analyses showed that the concentrations of phenolics indeed increased due to CO 2 enrichment.…”
Section: The Effect Of Abiotic Environmental Factorsmentioning
confidence: 99%